Integration of Social Assistance Benefit Recipients Into Labour Market: Monetary and Non-Monetary Factors - Straševičiūtė, Žeimantė; Lazutka, Romas (Socialinė teorija, empirija, politika ir praktika, 2026)
The article analyzes monetary and non-monetary factors that limit the employment of social assistance recipients. It reviews various aspects of how minimum income protection and activation systems are coordinated in foreign countries and in Lithuania. The authors present classifications used by other researchers and propose their own original framework for categorizing barriers to labor market integration. The results of a 2022 quantitative research on the employment barriers faced by unemployed social benefit recipients are presented. Data were analyzed using logistic binomial regression and correlation methods. The findings reveal that the most common causes of unemployment are beyond the control of the unemployed. The most significant barrier is the lack of job opportunities in the individual’s place of residence, combined with transportation difficulties. The assumption that relatively good material conditions of social benefit recipients discourage them from employment was not confirmed.
Keywords: activation policy; barriers to employment; social assistance recipients